Pregnancy-induced hypertension and infant growth at 28 and 42 days postpartum - Piedboeuf Bruno; Fraser William D; Baulon Emmanuelle; Buekens Pierre; Xiong Xu (BMC, 2005)
Abstract Background No previous studies have examined the effect of pregnancy-induced hypertension (PIH) on early infant growth. The objective was to study infant growth patterns of babies born to mothers with PIH at 28 and 42 days postpartum. Methods: Design We conducted a population-based retrospective cohort study of 16,936 pregnancies delivered between January 1, 1989 through December 31, 1990 in Suzhou, China. PIH was classified as gestational hypertension, preeclampsia and severe preeclampsia. Infant Growth Percentage (IGP) was calculated as the weight gain from birth to infant weight at 28 or 42 days postpartum divided by the birth weight. Univariate analysis and multivariate linear regression were performed to compare the infant weight as well as IGP at 28 and 42 days postpartum between various types of PIH and the normotensive group. Results Infant weights at 28 and 42 days postpartum were significantly lower in severe preeclampsia (e.g., 4679.9 g at 42 days) and preeclampsia (e.g., 4763.8 g at 42 days) groups than in the normotensive group (e.g., 4869.1 g at 42 days, p < 0.01). However, there were no differences in IGP between groups. After stratifying by intrauterine growth restriction (IUGR) status, if babies were not intrauterine growth restricted, none of the PIH types showed a significantly lower weight at 28 and 42 days postpartum and their IGPs were similar to those of the reference group. When babies were growth restricted, all PIH groups showed significantly lower weights but higher IGP at 28 and 42 days postpartum as compared to the normotensive group. Conclusion Infants born to mothers with PIH but without IUGR have normal early infant growth. IUGR secondary to PIH is associated with significant catch-up growth at 28 and 42 days postpartum.